Management of severe postictal agitation after electroconvulsive therapy with bispectrum electroencephalogram index monitoring: a case report - Kranaster, Laura; Janke, Christoph; Sartorius, Alexander (The journal of ECT, 2012)
Postictal agitation (PIA) with possible severe implications occurs in approximately 10% of electroconvulsive therapy (ECT) sessions. The pathomechanism is not well understood, and suggested treatments are empirical based. We report a case of repetitive (47/57 sessions [83%]) severe PIA after ECT in a case with severe depression. If the minimal bispectrum EEG index (BIS) value, meaning the deepest level of sedation of the thiopental narcosis dropped below 50, PIA occurred in only 9.1%. Bispectral index (BIS) monitoring made prediction and prevention of PIA possible to some degree. Postictal agitation might occur in vulnerable patients when initial depth of anesthesia is too light.